2013
DOI: 10.1021/jf4010059
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Atrazine Degradation Capability To Mineralize Aged 14C-Labeled Atrazine Residues in Soils

Abstract: The degradation of environmentally long-term aged (22 years) ¹⁴C-labeled atrazine residues in soil stimulated by inoculation with atrazine-adapted soil from Belgium, the United States (U.S.), and Brazil at two different moisture regimes (50% WHCmax/slurried conditions) was evaluated. Inoculation of the soil containing the aged ¹⁴C-labeled atrazine residues with 5, 50, and 100% (w/w) Belgian, U.S., or Brazilian atrazine-adapted soil increased ¹⁴C-atrazine residue mineralization by a factor of 3.1-13.9, dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Jones et al found that biochar suppresses simazine biodegradation and reduces simazine leaching [11]. However, Jablonowski et al observed that increased degradation of atrazine residues likely occurred through the transfer of atrazine-adapted soil microflora from different soils and regions to non-adapted soil [12]. Therefore, the influence of biochar on pesticides produces variable results.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al found that biochar suppresses simazine biodegradation and reduces simazine leaching [11]. However, Jablonowski et al observed that increased degradation of atrazine residues likely occurred through the transfer of atrazine-adapted soil microflora from different soils and regions to non-adapted soil [12]. Therefore, the influence of biochar on pesticides produces variable results.…”
Section: Introductionmentioning
confidence: 99%
“…It resists environmental degradation owing to a slow photolysis and hydrolysis rate [ 2 ]. It disrupts the photosynthetic (energy-producing) process in broadleaf weeds and annual grasses [ 3 ]. ATR has become the most frequently detected pesticide in surface water and groundwater [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, biochar soil amendments are attracting increasing attention from policy makers in China and other countries. However, types of biochar that have an exceptionally high sorption [10] or degradation [7,11] capacity for organic chemicals, especially pesticides, may have both positive and negative impacts on pest management. On the one hand, the high retentive qualities of biochar may prevent or reduce the leaching of soil-applied herbicides and insecticides [12,13] and may decrease the rate at which they are degraded by soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%